EVALUATING THE IMPACT OF UNIVERSAL HEALTHCARE POLICIES ON ACCESS TO CARE IN DEVELOPING COUNTRIES - Dr. Ingrid Hansen (Modern American Journals, 2025)
Universal healthcare (UHC) policies have become a cornerstone of healthcare reform in many developing countries, aiming to provide equitable access to healthcare services for all citizens. The implementation of UHC is often seen as a solution to the disparities in healthcare access, which are common in low- and middle-income countries. This paper evaluates the impact of universal healthcare policies on access to care in developing countries by analyzing both the successes and challenges faced in their implementation. It examines case studies from countries such as Thailand, Rwanda, and Ghana, where UHC policies have been introduced, focusing on how these policies have affected healthcare access, quality of care, and health outcomes. The paper also explores the role of financing mechanisms, healthcare infrastructure, and the involvement of the private sector in ensuring the effectiveness of UHC programs. The findings suggest that while UHC has improved healthcare access and outcomes in some countries, challenges such as funding, workforce shortages, and geographic disparities remain. This paper concludes with recommendations for policymakers to enhance the effectiveness of UHC policies in developing countries, including the importance of sustained investment, improved infrastructure, and inclusive governance.
Keywords: Universal healthcare, developing countries, access to care, healthcare policies, health systems, healthcare financing, health outcomes, equity, healthcare infrastructure, public health.